Leverage on Firm Value with Two Diversifying Profitability and Investment Opportunities - Preatmi Nurastuti; Ahmad Rasyiddin; Adrianna Syariefur Rakhmat (Journal of Research in Social Science and Humanities, 2025)
This research contributes to scientific studies on the contribution of leverage structure to increasing firm value using mediation: profitability and Investment Opportunity Set. This is relevant considering 1. The importance of the leverage function for the company, 2. Profitability and investment opportunities as mediation in increasing firm value are ignored in previous studies. 3. This study also replicates leverage for value creation mediated by IOS, considering that leverage is important for the financial health of the company to grow in creating firm value. This study will help policy makers to have a greater focus on creating firm value. The research analysis was conducted using path analysis, Sobel test, which is used to test the hypothesis from quantitative data taken from manufacturing companies listed on the Indonesia Stock Exchange. This study shows that leverage cannot affect firm value. Profitability also cannot affect firm value. However, leverage can affect profitability or the ability to generate profits as the company's profit power. The company's profit power has the potential to open up investment opportunities and increase firm value.